Decidability in complex social choices - Luigi Marengo; Davide Pirino; Simona Settepanella; Akimichi Takemura (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2012)
Recently, Marengo and Settepanella (2010) introduced a model of social choice among bundles of interdependent elements. In this paper we prove that their voting model is highly decidable, i.e. a group of agents that agrees to use such voting process has an high probability to reach a final decision. We also better qualify the degree of manipulability of such a final decision, showing that it is independent not only from the agenda, but also from the initial condition. Therefore we show that the Marengo and Settepanella (2010) model has nice properties of decidability and can be fruitfully used both for normative and positive analyzes of collective choices among complex interdependent elements.
Keywords: D03; D71; D72; 330; social rule; object; optimum; probability; tournament